Epigenetics in advanced renal cell carcinoma: Potential new targets. (December 2022) - Molina-Cerrillo, Javier; Santoni, Matteo; Ruiz, Álvaro; Massari, Francesco; Pozas, Javier; Ortego, Ignacio; Gómez, Victoria; Grande, Enrique; Alonso-Gordoa, Teresa
Abstract: Renal cell carcinoma (RCC) is the seventh most frequently diagnosed tumor in adults in Europe and represents approximately 2.5 % of cancer deaths. In metastatic setting, clinical strategies including angiogenesis inhibition with tyrosine kinase inhibitors, as well as immunotherapy against immune checkpoint proteins, such as PD-1/PDL-1 and CTLA-4, have revolutionized the treatment landscape. Unfortunately, most patients progress to anti angiogenic and immunotherapy treatment. Epigenetic aberrations are commonly found in RCC, showing that changes in epigenetic modifications, like promoter methylation or abnormal microRNA expression, are key in the development of RCC due to gene expression alterations without changes in the genome sequence. Nowadays, new drugs in the field of epigenetics are able to modify gene expression to induce antitumoral effect in the tumor cell. In kidney cancer, drugs targeting epigenetics are in early development, but could be promising in the near future. In this review, we summarize the main epigenetic alterations found in RCC and their involvement in pathological signaling pathways, being a new potential target that could potentially be added to the treatment flow of patients with advanced RCC. Graphical Abstract: ga1 Highlights: Kidney cancer represents the third tumor most frequently diagnosed in the urinary tract in adults. Epigenetic modifications are key in the development of RCC due to gene expression alterations. In kidney cancer, drugs targeting epigenetics are at their early development, but could be promising in the near future. Many trials are under development in RCC patients with promising results, with drugs such as vorinostat or azacytidine.